Performance Evaluation of Cassava Starch as Concrete Admixture - Usman, Seidu Abuh; Abubakar, Aliyu; Olubunmi, Adetoye (Journal of Multidisciplinary Research Advancements, 2024)
Concrete is a composite material and the most widely used construction material. It comprises cement, aggregates, and water for hydration purposes. Recently, rapid increases in the cost of construction and problems associated with the use of cement, a major constituent of concrete, have necessitated the search for supplementary cementitious materials in partial replacement of cement in construction works. Admixtures are integrated into concrete to solve problems and improve the properties of both fresh and hardened concrete. This research evaluates the performance of concrete containing cassava starch as a mineral admixture. A face-centered cubic central composite response surface design was used to investigate the effects of cassava starch on the compressive strength of concrete at 3, 14, and 28 days, respectively. The cassava starch admixture was varied in the range of 0.1 to 0.5% by weight of cement. The effect of cassava starch on the compressive strength of concrete was studied at a constant water-binder ratio of 0.5, using response surface generated by the Design- Expert software 13. The results indicate maximum compressive strengths of the admixed concrete at 0.1% of cassava starch content. It was presumed from a review of related literature that the compressive strength of concrete decreases with an increase in the cassava starch content of the concrete mix. The assumption was found to be correct based on the compressive strength test that was conducted on the cubes with varying cassava starch content (0%, 0.1%, 0.2%, 0.3%, 0.4% and 0.5%). Numerical optimization was conducted, and model equations were generated for concrete with starch as an admixture. 0.1% of cassava starch is recommended as an admixture in concrete production, and, certain admixtures such as air-entraining agents and superplasticizers should be used so as to improve the flow properties of concrete.